Melatonin improves quality and longevity of chronic neural recording. (October 2018) - Golabchi, Asiyeh; Wu, Bingchen; Li, Xia; Carlisle, Diane L.; Kozai, Takashi D.Y.; Friedlander, Robert M.; Cui, Xinyan Tracy
Abstract: The chronic performance of implantable neural electrodes is hindered by inflammatory brain tissue responses, including microglia activation, glial scarring, and neuronal loss. Melatonin (MT) has shown remarkable neuroprotective and neurorestorative effects in treating central nervous system (CNS) injuries and degeneration by inhibiting caspase-1, -3, and -9 activation and mitochondrial cytochrome c release, as well as reducing oxidative stress and neuroinflammation. This study examined the effect of MT administration on the quality and longevity of neural recording from an implanted microelectrode in the visual cortex of mice for 16 weeks. MT (30 mg/kg) was administered via daily intraperitoneal injection for acute (3 days before and 14 days post-implantation) and chronic (3 days before and 16 weeks post-implantation) exposures. During the first 4 weeks, both MT groups showed significantly higher single-unit (SU) yield, signal-to-noise ratio (SNR), and amplitude compared to the vehicle control group. However, after 4 weeks of implantation, the SU yield of the acute treatment group dropped to the same level as the control group, while the chronic treatment group maintained significantly higher SU yield compared to both acute (week 5–16) and control (week 0–16) mice. Histological studies revealed a significant increase in neuronal viability and decrease in neuronal apoptosis around the implanted electrode at week 16 in the chronic group in comparison to control and acute subjects, which is correlated with reduced oxidative stress and increased number of pro-regeneration arginase-1 positive microglia cells. These results demonstrate the potent effect of MT treatment in maintaining a high-quality electrode-tissue interface and suggest that MT promotes neuroprotection possibly through its anti-apoptotic, anti-inflammatory, and anti-oxidative properties.